THE EFFECT OF HIGH ENERGY ELECTROMAGNETIC PULSES ON SEISMICITY IN CENTRAL ASIA AND KAZAKHSTAN - Tarasov N.T.; Tarasova N.V.; Avagimov A.A.; Zeigarnik V.A. (My University, 2000)
The effect of high-energy electromagnetic pulses emitted by a magnetohydrodynamic (MHD) generator on the seismicity of former Soviet Central Asia and Kazakhstan is examined. The seismicity was found to be appreciably higher in the area of study after the MHD-generator start-ups than before them. A sharp increase in the local seismicity rate began 2-4 days after the start-ups and continued during a few days afterward. It is shown that electromagnetic pulses initiate the release of the energy, stored in the earth during tectonic processes, in the form of comparatively small earthquakes.